2015
DOI: 10.4103/0255-0857.148831
|View full text |Cite
|
Sign up to set email alerts
|

Performance of rapid influenza diagnostic tests (QuickVue) for Influenza A and B Infection in India

Abstract: Background Rapid point-of-care (POC) tests provide an economical alternative for rapid diagnosis and treatment of influenza, especially in public health emergency situations. Objectives To test the performance of a rapid influenza diagnostic test, QuickVue (Quidel) as a POC test against a real-time polymerase chain reaction (RT-PCR) assay for detection of influenza A and B in a developing country setting. Study Design In a prospective observational design, 600 patients with influenza-like illness (ILI) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Most of the included studies were performed in children, especially those evaluating rapid tests for RSV, which at least partly explains the lack of influence of age on the diagnostic accuracy estimates for RSV. For influenza, however, rapid test performance was significantly better in children, as reported elsewhere [24,25]. Age is inversely associated with viral load, which may explain better test results in children.…”
Section: Main Findings Of the Studysupporting
confidence: 75%
“…Most of the included studies were performed in children, especially those evaluating rapid tests for RSV, which at least partly explains the lack of influence of age on the diagnostic accuracy estimates for RSV. For influenza, however, rapid test performance was significantly better in children, as reported elsewhere [24,25]. Age is inversely associated with viral load, which may explain better test results in children.…”
Section: Main Findings Of the Studysupporting
confidence: 75%
“…In addition, patients with positive RIDTs were not confirmed by PCR, so the false-positivity rate for influenza in our study is unknown. Several other studies, however, have evaluated the Quidel QuickVue AϩB assay and found it to have specificities greater than 97% for influenza A and B compared to RT-PCR (22)(23)(24). Based on this, we would estimate around seven false positives in our patient cohort.…”
Section: Discussionmentioning
confidence: 84%
“…This indicates that the immunochromatographic test would frequently show false negatives because the IAV copy number can be less than the detection limit of the assay [6]. Indeed, a clinical study showed that most patients are misdiagnosed as negative for influenza virus based on initial testing using immunochromatography [33]. Alternative methods such as RT-qPCR on Roche's cobas Liat System have been developed to address this issue [14].…”
Section: Discussionmentioning
confidence: 99%